Write Idea - Aoki, Eleine Mei and Flood, James (New York Macmillan/McGraw-Hill School Publishing Company, 1993)
Write Idea! is organized into three parts; you can read about the three parts and what is in each part. Part One: Writers and Writing. Part Two: Writers Workshop. Part Three: Information Instantly.
Keywords: Writing